Steroid-Resistant Nephrotic Syndrome due to NPHS2 Variants Is Not Associated With Posttransplant Recurrence - Jessica Kachmar; Olivia Boyer; Beata Lipska-Ziętkiewicz; Vincent Morinière; Olivier Gribouval; Laurence Heidet; Irena Balasz-Chmielewska; Elisa Benetti; Sylvie Cloarec; Dagmar Csaicsich; Stéphane Decramer; Jutta Gellermann; et al. (Kidney International Reports)
Introduction: Unlike idiopathic nephrotic syndrome (NS), hereditary podocytopathies are not expected to recur after kidney transplantation. However, some reports of posttransplant recurrence of NS in patients carrying variants in the NPHS2 gene have been described, notably with the p.Arg138Gln variant, which is more prevalent in Europe. The objective of this study was to assess the risk of recurrence after kidney transplantation in a large cohort of patients with biallelic NPHS2 pathogenic variants. Methods: Since January 2010, 61 patients identified at Necker-Enfants Malades Hospital and 56 enrolled in the PodoNet Registry with biallelic variants in the NPHS2 gene were transplanted and were compared with 44 transplanted children with steroid-resistant NS (SRNS) without any identified pathogenic variant. Results: Of the 117 patients, 23 carried the p.Arg138Gln variant in the homozygous state and 16 in the compound heterozygous state. The other 78 patients carried different variants in the homozygous (n = 44) or compound heterozygous state. Only 1 patient with NPHS2-related SRNS experienced posttransplant recurrence (median follow-up of cohort 8.5 years [2.5–15]). Conversely, 7 of 44 patients (16%) without any identified pathogenic variant recurred within a maximum of 7 days after transplantation (median follow-up 8.9 years [0.6–13.9]). Conclusion: In this large cohort, the risk of patients with causative variants in the NPHS2 gene to develop NS recurrence after kidney transplantation was extremely low. This is coherent with the pathophysiology of intrinsic slit-diaphragm disease. These data are reassuring and should be considered when counselling patients, making living kidney donation, whether related or not, a safe choice.